A Sociocognitive Perspective on Second Language Classroom Willingness to Communicate. Issue 4 (17th January 2014) - Cao, Yiqian (Katherine)
<x xml:space="preserve">Abstract</x> This article reports on a multiple case study that investigated the dynamic and situated nature of learners' willingness to communicate (WTC) in second language (L2) classrooms. Framed within a sociocognitive perspective on L2 learning which draws together social, environmental, and individual factors, this study traced WTC among six learners of English as a second language enrolled in an English for academic purposes programme in New Zealand for 5 months. Data were collected through classroom observations, stimulated‐recall interviews, and reflective journals. Analysis of the data suggests that the classroom WTC construct is best described as a dynamic situational variable rather than a trait disposition. This article argues that situational WTC in class results from the interdependence among individual characteristics, classroom environmental conditions, and linguistic factors. These three strands of factors interdependently exert either facilitative or inhibitive effects on an individual student's WTC in class at any point in time. The effect of the combinations of factors differs between individuals, and the interrelationship is too complex to be predicted.